LISTENING IS A CORNERSTONE OF LEARNING ENGLISH LANGUAGE - MAKSUDOV, Umed Olimovich (The Lingua Spectrum, 2025)
In the article, you will find the answer to the question: how exactly the students are trained in comprehension of English speech. The tasks that need to be solved by the teacher to make listening the most effective are described. Special attention is paid to the advantages of using audio materials when students are involved in different activities. However, the modern education system is competent in this matter, they pay considerable attention to the process of perception through listening and other effective methods at universities. The audio text is a text for semantic listening. It is one of the leading forms of student learning, as audio texts are extremely realistic based on life events. The article argues the problems of students' understanding of listening. It is proposed the ways of analyzing the listening process to find the most effective points of approach directly to the process. Exactly the methods and their productivity enables the student to master foreign language speech. Passive listening really brings benefits, students get used to the sound of foreign speech and unconsciously learn the pronunciation, but for more success, they need to listen and work on their lacks. Pursuing a specific goal, they can be sure that the exercise will not pass in vain. According to the latest research in the field of listening, different students behave identically while listening to foreign speech. This fact makes it possible to predict their behavior. The teacher only needs to properly organize the listening process. It is written in the work of Shankar, who conducted a number of tests among students of foreign speech.